1996
DOI: 10.1037/0882-7974.11.3.454
|View full text |Cite
|
Sign up to set email alerts
|

Adult age differences in the use of distractor homogeneity during visual search.

Abstract: Previous research has suggested that an age-related decline may exist in the ability to inhibit distracting information during visual search. The present experiments used a conjunction search task in which the within-item features of the target (an upright L) and the distractors (rotated Ls) were identical. In each of 2 experiments, both young and older adults searched the display significantly more rapidly when the distractors were all rotated in the same direction (homogeneous) than when the distractors were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
76
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 33 publications
(126 reference statements)
17
76
1
Order By: Relevance
“…Older adults' preserved ability to improve performance in this task supports previous investigations of visual search that used variation in the featural composition of the displays to elicit top-down control (Humphrey & Kramer, 1997;Madden et al, 1996). The data for nonsingleton targets are consistent with previous research indicating that under some conditions attentional capture by a singleton is more pronounced for older adults than for younger adults (Kramer et al, 2000;Pratt & Bellomo, 1999).…”
Section: Discussionsupporting
confidence: 86%
“…Older adults' preserved ability to improve performance in this task supports previous investigations of visual search that used variation in the featural composition of the displays to elicit top-down control (Humphrey & Kramer, 1997;Madden et al, 1996). The data for nonsingleton targets are consistent with previous research indicating that under some conditions attentional capture by a singleton is more pronounced for older adults than for younger adults (Kramer et al, 2000;Pratt & Bellomo, 1999).…”
Section: Discussionsupporting
confidence: 86%
“…This type of age-related change has been observed frequently under resource-limited conditions and can be accounted for by general (relatively task-independent) changes in the speed of visual information processing (Madden, 2001;Madden et al, 1996;Plude & Hoyer, 1986). It is also interesting to note that the degree of age-related slowing, in terms of the ratio of older adults' RT slopes to those of the younger adults, decreased markedly from Experiment 1 (1.71) to Experiment 2 (1.25).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other studies that used time constraints for stimulus presentation and reported global precedence effects (Navon, 1977;Slavin et al, 2002;Weissman et al, 2002), stimuli in the present study remained on the screen until the subject pressed the response button. This procedure ensured sufficient processing time for older participants, who commonly have prolonged RTs (Cabeza, 2001;Madden et al, 1996;Salthouse, 1996) as they did herein, but may also have afforded time to process beyond the global level. Further, in our paradigm black local letters were superimposed on a gray global letter presented on white background.…”
Section: Precedence Effectsmentioning
confidence: 99%
“…Earlier accounts assumed that such interference results from the processing priority of global features, i.e., global precedence, in which processing at the global level either precedes or finishes earlier than processing at the local level (e.g., Navon, 1977). Current theories assume parallel and concurrent processing of the different dimensions of local-global stimuli (Hoffman, 1980;Madden et al, 1996), where global interference arises from the inhibition of local pathways by those carrying global information (Christman, 2001;Hughes, 1986;Kitterle et al, 1993). Evidence from brain lesion studies (Delis et al, 1986(Delis et al, ,1988Robertson et al, 1988Yamaguchi et al, 2000) and neuroimaging studies in healthy participants (Evans et al, 2000;Fink et al, 1996Fink et al, ,1999Han et al, 2002;Weber et al, 2000;Yamaguchi et al, 2000) indicates that local and global processing proceeds in parallel, with the left hemisphere assuming a local and the right hemisphere a global processing advantage.…”
Section: Introductionmentioning
confidence: 99%